Dynamics of the scissors-type Mobile Bridge. (2017) - Chikahiro, Yuki; Ario, Ichiro; Pawlowski, Piotr; Graczykowski, Cezary; Nakazawa, Masatoshi; Holnicki-Szulc, Jan; Ono, Syuichi
Abstract: We have experienced many times a phenomenon in which a bridge is washed away due to a typhoon, heavy rain in the rainy season, localized torrential rain, tsunami, and other flood disasters, or in which a bridge is damaged by an earthquake or a tremor. There is accordingly increasing demand for new technology and science to restore bridges that have been washed away or damaged. The paper presents a new type of emergency bridge, called Mobile Bridge™(MB), which can be quickly constructed in case of damages after a natural disaster. The concept of the bridge is based on the application of scissor-type mechanism, which provides its rapid deployment. Up to now several experimental MBs of different size were constructed and tested. The presented research reviews fundamental numerical and experimental results for the MB version 4.0 (MB4.0). Experimental testing included strain and acceleration measurements in free and forced loading conditions. From these results, it was possible to estimate basic dynamic characteristics of the bridge. Besides, in order to provide a basis for development of new construction methods for structural reinforcement and suppression of vibrations, various numerical analyses were conducted. The conducted research allows for a better and safer design of the movable and foldable full-scale bridge, the MB.